INTERCULTURAL HARMONY AND RELIGIOUS TOLERANCE AS THE CONSTITUTIONAL BASIS OF UZBEKISTAN’S STATEHOOD STABILITY - Arziev , Samug’ (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This article analyzes the role of interethnic harmony and religious tolerance in the stability of statehood in the Republic of Uzbekistan from a constitutional-legal perspective. The theoretical and practical aspects of the issue are explored based on the relevant articles of the Constitution of the Republic of Uzbekistan, norms and standards of international law, as well as the scholarly views of leading national and foreign experts. Furthermore, the existing legislative system regulating national and religious relations in Uzbekistan and its significance in modern state-building are extensively covered.